2014
DOI: 10.1155/2014/694193
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Adjuvant Zinc Therapy on Recovery from Pneumonia in Hospitalized Children: A Double-Blind Randomized Controlled Trial

Abstract: Objectives. Pneumonia is one of the common mortality causes in young children. Some studies have shown beneficial effect of zinc supplements on treatment of pneumonia. The present study aimed to investigate the effects of short courses of zinc administration on recovery from this disease in hospitalized children. Methods. In a parallel Double-Blind Randomized Controlled Trial at Ayatollah Golpaygani Hospital in Qom, 120 children aged 3–60 months with pneumonia were randomly assigned 1 : 1 to receive zinc or pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 12 publications
0
24
0
2
Order By: Relevance
“…Supplementation depends upon a viable delivery system with built-in quality control, as well as wide coverage and high acceptance rates among vulnerable individuals and families [ 9 ]. Moreover, supplemental administration of zinc can expedite the healing process and results in faster resolution of clinical symptoms in children with pneumonia [ 38 ]. In Iran, the government has been supplementing iron to school girls and has started supplying vitamin D to them [ 39 ].…”
Section: Prevention and Control Of Mndsmentioning
confidence: 99%
“…Supplementation depends upon a viable delivery system with built-in quality control, as well as wide coverage and high acceptance rates among vulnerable individuals and families [ 9 ]. Moreover, supplemental administration of zinc can expedite the healing process and results in faster resolution of clinical symptoms in children with pneumonia [ 38 ]. In Iran, the government has been supplementing iron to school girls and has started supplying vitamin D to them [ 39 ].…”
Section: Prevention and Control Of Mndsmentioning
confidence: 99%
“…Multiple human trials have shown conflicting evidence for zinc supplementation improving outcomes in patients with pneumonia. In some cases, zinc supplementation shortened the duration of viral infections and improved outcomes in children with lower respiratory infections [ 60 , 96 98 ] but not in others [ 99 ], and even in some cases for elderly patients with pneumonia [ 100 ] but not in others [ 52 ]. In addition to undernourished children and the elderly, vegan and vegetarian populations are particularly susceptible to zinc deficiency, as plant-based diets will contain more phytates which are known to interfere with zinc bioabsorption [ 44 , 45 , 101 , 102 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zinc supplementation given with empiric antimicrobial therapy significantly shortened the duration of hospital stay for young children with pneumonia [22]. Iqbal et al also reported similar results from Pakistani children [23], Qasemzadeh et al from Iran reported significant decrease was found in the duration of hospitalization and recovery from severe pneumonia symptoms in zinc receiving children [24]. In contrast two trails from Nepal demonstrated that adjuvant zinc neither reduced the risk of treatment nor hasten the recovery from non-severe or severe pneumonia in Nepalese children in the age group of 2-35 months of age [20].…”
Section: Discussionmentioning
confidence: 63%